34.4k views
1 vote
Find the distance between the points (-3,2) and (0,3).

2 Answers

2 votes

Answer:

The distance between (-3, 2) and (0,3) is √10.

Explanation:

As we go from (-3,2) to (0,3), x increases by 3 and y increases by 1.

Think of a triangle with base 3 and height 1. Use the Pythagorean Theorem to find the length of the hypotenuse, which represents the distance between the points (-3, 2) and (0, 3):

distance = √(3² + 1²) = √10

The distance between (-3, 2) and (0,3) is √10.

User CAD
by
5.7k points
1 vote

For this case we have that by definition, the distance between two points is given by:


d = \sqrt {(x_ {2} -x_ {1}) ^ 2+ (y_ {2} -y_ {1}) ^ 2}

We have the following points:


(x_ {1}, y_ {1}): (- 3,2)\\(x_ {2}, y_ {2}) :( 0,3)

Substituting:


d = \sqrt {(0 - (- 3)) ^ 2+ (3-2) ^ 2}\\d = \sqrt {(3) ^ 2 + (1) ^ 2}\\d = \sqrt {9 + 1}\\d = \sqrt {10}

Answer:

The distance between the points is
\sqrt {10}

User DoomageAplentty
by
5.4k points